Characithecium spp. (Monogenea: Dactylogyridae) from Astyanax bimaculatus (Characiformes: Characidae) in Northeast Brazil, with Description of a New Species - da Silva, Bruno Anderson Fernandes; da Silva, Reinaldo José [UNESP]; Yamada, Fábio Hideki (Springer Nature, 2021)
Purpose: To date, seven species of Characithecium Mendonza-Franco, Reina and Torchin, 2009 (Monogenea, Dactylogyridae) are valid, parasitizing mainly fishes of the family Characidae (Characiformes) in the Neotropical region. During a parasitological study of fishes in the Batateiras River and Carás stream, Ceará state, Brazil, two species of Characithecium were collected from the gills of Astyanax bimaculatus Linnaeus, 1758 (Characidae). The purpose of the present study is to describe a new species of monogenean of the genus Characithecium and report Characithecium costaricensis Mendoza-Franco, Reina and Torchin, 2009 in A. bimaculatus, in Brazil. Methods: Monogeneans were isolated from the gills and stored in 70% ethanol, mounted in Gray and Wess’ medium or and in a mixture of glycerin ammonium picrate (GAP) to study sclerotized structures. Morphological analyses were performed with a computerized image analysis system with differential interference contrast (DIC). The drawings were obtained with the aid of a camera lucida mounted on a Leica DMLS microscope. Results: Characithecium bifurcuprolatum n. sp. differs from its congenerics by the morphology of the accessory piece having a ventral unit articulated to cirrus base, a non-articulated dorsal and mid-ventral, and a sclerotized vaginal vestibule. Characithecium costaricensis was described from Astyanax aeneus (Günther, 1860) (Characidae) in Central America, and the present finding represents a new geographical and host records in Brazil. Furthermore, we observed the presence of a membrane at the base of the cirrus not mentioned in the original description. Conclusion: Our findings increase to eight the number of known species of the genus Characithecium parasitizing characids in neotropics. We verified some additional characteristics present in the two species studied, such as the presence of a membrane at the base of the cirrus, an accessory piece with two subunits (an articulated ventral and a dorsal non-articulated) and the presence of sclerotized vaginal vestibule.
Keywords: Ancyrocephalinae; Biodiversity; Caatinga; Fish parasites; Salgado River basin